1981
DOI: 10.1111/j.1469-8137.1981.tb04095.x
|View full text |Cite
|
Sign up to set email alerts
|

OVULE DEVELOPMENT IN ORNITHOGALUM CAUDATUM (LILIACEAE) WITH A REVIEW OF SELECTED PAPERS ON ANGIOSPERM REPRODUCTION

Abstract: SUMMARYThe chalazal end of the egg projects beyond the synergids while the micropylar end is in contact with the nucellar epidermis. The egg nucleus and nucleolus are large and, along with most of the cytoplasm, are located chalazally while a large vacuole occupies the micropylar end. The egg cell wall is attenuated chalazally but, based on preliminary light microscope observations, it does appear to surround the entire cell in some cases. The synergids each have a large chalazal vacuole with the majority of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 98 publications
0
32
1
Order By: Relevance
“…In Epidendum scutella (Cocucci & Jensen 1969), Papaver nudicaule (Olson & Cass 1981) and Scilla sibirica sato (Bhandari & Sachdeva 1983) the cells of the egg apparatus are entirely involved by PAS-positive walls. Tilton (1981) equally observed continuous walls around the egg apparatus of Ornithogalum caudatum in some optical preparations. In Epidendrum scutella, in the chalazal portion of the degenerative synergid, common walls between egg and central cells are dissolved, so that the last two cells establish direct contact with the degenerative synergid (Cocucci & Jensen 1969).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Epidendum scutella (Cocucci & Jensen 1969), Papaver nudicaule (Olson & Cass 1981) and Scilla sibirica sato (Bhandari & Sachdeva 1983) the cells of the egg apparatus are entirely involved by PAS-positive walls. Tilton (1981) equally observed continuous walls around the egg apparatus of Ornithogalum caudatum in some optical preparations. In Epidendrum scutella, in the chalazal portion of the degenerative synergid, common walls between egg and central cells are dissolved, so that the last two cells establish direct contact with the degenerative synergid (Cocucci & Jensen 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Many ultrastructural studies have demonstrated that the synergids are very active cells, probably involved in the secretion of substances -e.g., chemiotactic substances which guide the pollen tube to the synergids, as well as in the absorption of nutritious material originating from tissues of the micropylar region and its translocation to the central and egg cells (Schulz & Jensen 1968, Tilton 1981, Willemse & van Went 1984, Folsom & Cass 1990, Mansfield et al 1991, Russell 1992, Tirlapur et al 1993. According to this vision, the filiform apparatus exercises the important function of increasing diffusion efficiency, like wall ingrowths of transfer cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to Cass (1972) and Cass and Karas (1974), the egg of Plumbago has both gametic and synergid functions. However, based on organelle content, the typical egg seems to be a passive cell that functions only as the female gamete (Jensen, 1974;Tilton, 1981b).…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…There are a few reports in which wall material has been said to occur as disjunct islands in the chalazal end of the cell and, in Bellis, Fngell and Petersen (1977) reported that the wall is entire. Preliminary light microscopic (LM) investigations indicate that the wall may be entire in Ornithogalum caudatum as well (Tilton, 1981b).…”
Section: Introduction and Reviewmentioning
confidence: 99%
See 1 more Smart Citation